Flare on [18F]PSMA-1007 PET/CT after short-term androgen deprivation therapy and its correlation to FDG uptake: possible marker of tumor aggressiveness in treatment-naïve metastatic prostate cancer patients - Malaspina Simona; Ettala Otto; Tolvanen Tuula; Rajander Johan; Eskola Olli; Boström Peter J.; Kemppainen Jukka (SPRINGER, 2022)
Purpose Short-term androgen deprivation therapy (ADT) is known to increase heterogeneously prostate-specific membrane antigen (PSMA) expression. This phenomenon might indicate the potential of cancer lesions to respond to ADT. In this prospective study, we evaluated the flare on [F-18]PSMA-1007 PET/CT after ADT in metastatic prostate cancer (PCa). Given that aggressive PCa tends to display FDG uptake, we particularly investigated whether the changes in PSMA uptake might correlate with glucose metabolism.
Methods Twenty-five men with newly diagnosed treatment-naive metastatic PCa were enrolled in this prospective registered clinical trial. All the patients underwent [F-18]PSMA-1007 PET/CT immediately before and 3-4 weeks after ADT initiation (degarelix). Before ADT, [F-18]FDG PET/CT was also performed. Standardized uptake values (SUV)max of primary and metastatic lesions were calculated in all PET scans. Serum PSA and testosterone blood samples were collected before the two PSMA PET scans. The changes in PSMA uptake after ADT were represented as Delta SUVmax.
Results All the patients reached castration levels of testosterone at the time of the second [F-18]PSMA-1007 PET/CT. Overall, 57 prostate, 314 lymph nodes (LN), and 406 bone lesions were analyzed. After ADT, 104 (26%) bone, 33 (11%) LN, and 6 (11%) prostate lesions showed an increase (>= 20%) in PSMA uptake, with a median Delta SUVmax of + 50%, + 60%, and + 45%, respectively. Among the lesions detected at the baseline [F-18]PSMA-1007 PET/CT, 63% bone and 46% LN were FDG-positive. In these metastases, a negative correlation was observed between the PSMA Delta SUVmax and FDG SUVmax (p < 0.0001). Moreover, a negative correlation between the Delta SUVmax and the decrease in serum PSA after ADT was noted (p < 0.0001).
Conclusions A heterogeneous increase in PSMA uptake after ADT was detected, most evidently in bone metastases. We observed a negative correlation between the PSMA flare and the intensity of glucose uptake as well as the decrease of serum PSA, suggesting that lesions presenting with such flare might potentially be less aggressive.